Antecedents and consequences of upward and downward social comparisons: An investigation of Chinese employees. Issue 1 (14th March 2016) - Foley, Sharon; Ngo, Hang-yue; Loi, Raymond
Abstract : Purpose: – The purpose of this paper is to extend and test a theory of uncertainty and directional social comparisons. Prior studies have posited that uncertainty leads to increased upward and downward social comparisons. The authors ' view is that uncertainty affects upward and downward comparisons differentially. They test their theory in the Chinese workplace, and focus specifically on employees' comparisons of career progress. Workplace consequences of social comparisons are also investigated. Design/methodology/approach: – The authors achieve their objectives by collecting data from respondents in China that measure uncertainty, directional social comparisons, organizational commitment and job satisfaction. They use a longitudinal design to assess causality. Findings: – This paper found that perceived organizational support, an antecedent that lowers uncertainty in the workplace, is related to upward social comparison, whereas psychological entitlement, an uncertainty-raising antecedent, is related to downward social comparison. Upward social comparison positively affected organizational commitment, whereas downward social comparison positively impacted job satisfaction. Research limitations/implications: – The data collection relied on self-reports and hence the findings may be adversely affected by common method bias. Another limitation involves the generalizability of results, given that the respondents were drawn from three large firms in China. Originality/value: – This paper indicates that directional social comparison processes serve as an important mechanism for understanding how employees' work attitudes are developed. It also demonstrates the applicability of social comparison theory to the study of organizational behavior in China.